Morphological complexity - Baerman, Matthew; Brown, Dunstan; Corbett, Greville G. (Cambridge Studies in Linguistics, 2017)
This book characterises the diverse morphological complexity we find in the languages of the world. Richly illustrated, examples are drawn from dozens of different languages and are subjected to rigorous quantitative analysis. It will be ideal reading for academic researchers and graduate students of linguistics, with a special interest in morphology and English language